Qualitative Descriptive Study of Adolescent Virtual Identity Through Instagram Social Media at SMAN 1 Depok - Arrahman, Khalifi; Santoso, Didik Haryadi (PT FORMOSA CENDEKIA GLOBAL, 2024)
The rapid proliferation of social media platforms like Twitter, Facebook, and Instagram has significantly impacted teenage behavior, particularly in terms of virtual identity creation. This study delves into how teenagers at SMAN 1 Depok utilize Instagram to craft their virtual personas, drawing on Michael Hecht’s Communication Theory of Identity. Employing a descriptive qualitative methodology, including observation, documentation, and interviews, this research zeroes in on female students at SMAN 1 Depok. Utilizing Von Eckartsberg’s phenomenological analysis, which encompasses data reduction, presentation, and conclusion drawing, the study identifies four distinct layers at which virtual identity is constructed: 1) The personal layer, evident in usernames and profiles across primary and secondary accounts; 2) The enactment layer, reflected in interactions like likes and comments from followers; 3) The relational layer, where usage of both accounts reveals different facets of identity—with the primary account showcasing a positive self-concept and limited identity disclosure, and the secondary account allowing for more open expression with selective friendships; 4) The communal layer, where identities are shaped within influencer or celebgram fan communities, with informants often swayed by prevalent lifestyles to gain acceptance. This research underscores the nuanced ways in which teenagers navigate their identities in the digital realm.